Description Of The Accuracy Of The Diagnostic Code For Hospitalized Medical Records Based On Icd 10 In Dharma Yadnya General Hospital - Ni Made Lia Tirtayanti (Politeknik Kesehatan Kartini Bali, 2021)
A medical record is a file containing a person's medical records and documents consisting of the patient's identity, the results of both physical examinations and supporting examinations, medication, actions and other services provided by health workers to patients. The purpose of this study was to describe the accuracy of writing a diagnosis code on the medical records of inpatients based on ICD-10. Demographic variables include age, gender and education of 2 respondents including the following: 1 respondent is over 30 years old while 1 other respondent is under 30 years old, 2 respondents are female, and 1 respondent medical record education graduate, while 1 other respondent is non-medical record. 1 respondent has a new category of service period, while 1 other respondent has a long service category. 2 respondents have knowledge value in good category about the accuracy of writing the diagnosis code. 2 respondents have attended training. There were 67,7% medical records with writing the correct diagnosis code and there were 32,3% medical records. by writing an incorrect diagnosis code were not found or the identity of the coder officer coding on the medical record sheet was not found, so the researcher could not find out the coding error of each coder officer who provided the diagnosis code.